Premature infants receiving delayed cord clamping with and without cord milking: a randomized control trial - Sariya Prachukthum; Chamnan Tanprasertkul; Charintip Somprasit (BMC, 2023)
Abstract Background Preterm infants often have long hospital stays and frequent blood tests; they often develop anemia requiring multiple blood transfusions. Placental transfusion via delayed cord clamping (DCC) or umbilical cord milking (UCM) helps increase blood volume. We hypothesized umbilical cord milking (UCM), together with DCC, would be superior in reducing blood transfusions. Objectives To compare the effects of DCC and DCC combined with UCM on hematologic outcomes among preterm infants. Methods One hundred twenty singleton preterm infants born at 280/7- 336/7 weeks of gestation at Thammasat University Hospital were enrolled in an open-label, randomized, controlled trial. They were placed into three groups (1:1:1) by a block-of-three randomization: DCC for 45 s, DCC with UCM performed before clamping (DCM-B), and DCC with UCM performed after clamping (DCM-A). The primary outcomes were hematocrit levels and number of infants receiving blood transfusions during the first 28 days of life. Intraventricular hemorrhage (IVH) and necrotizing enterocolitis (NEC) were secondary outcomes. Analyses were performed with an intent-to-treat approach. Results One hundred twenty preterm infants were randomized. There was no statistically significant difference in neonatal outcomes; hematocrit on admission 54.0 ± 5.5, 53.3 ± 6.0, and 54.3 ± 5.8 (p = 0.88), receiving blood transfusions 25%, 20%, and 12.5% (p = 0.24), incidence of NEC 7.5, 0 and 10% (p = 0.78) in the DCC, DCM-B and DCM-A groups, respectively. There were no preterm infants with severe IVH, polycythemia, maternal or neonatal death. Conclusion The placental transfusion techniques utilized, DCC and DCC combined with UCM, provided the same benefits for preterm infants born at GA 28 and 33 weeks in terms of reducing the need for RBC transfusions, severities of IVH and incidence of NEC without increasing comorbidity. Trial registration TCTR20190131002 . Registered 31 January 2019-Retrospectively registered.